Publicidade nativa como prevenção do banner blindness - Nunes, Patrícia Sampaio (2020)
The digital revolution has given rise to the emergence of new technological platforms, including social platforms - social media - in which audiences and brands can interact instantly. Due to the growing power of control of the user due to the different phases of the web, advertisers and marketing and communication managers are essentially faced with two significant problems: avoiding consciously or unconsciously (Banner Blindness phenomenon) and blocking advertisements by the of users. The object of study of this work is Native Advertising as a way to prevent the phenomenon of Banner Blindness, in social media, a theme that was worked on in the master’s dissertation. The theoretical and conceptual framework of the theme aims to understand how it came to Native Advertising in social media and how this type of advertising has allowed to escape the fact that digital advertising is ignored or even blocked by consumers. The methodology used was based on the review of the narrative literature. The results, recovered from the analysis of the existing literature, suggest a lack of information regarding the importance of advertising on the web, since users are irritated by viewing advertisements both surfing the web and on social media (Facebook, Twitter, Instagram, Youtube, among others), but they usually accept cookies that serve specifically for this purpose. The results also indicate that the relevance of the content is the key to success in order to capture the consumer’s attention in the digital environment.